Creating of interactive communication project (“Mindfulness Map” by the “7Mind” company) - Martiukhina, К. (ХДАК, 2023)
Interactive communication involves the sharing of information back and forth between sender and receiver in real time. It’s used in cases where an immediate response is required, and in other areas where push and pull communication methods seem insufficient. Interactive communication can be performed virtually or in person.
Keywords: спілкування інтерактивне; interactive communication